Identification of Meat Species by Polymerase Chain Reaction (PCR) Technique - İlhak, O. İrfan; Arslan, Ali (My University, 2007)
The origin of horse, dog, cat, bovine, sheep, porcine, and goat meat was determined by the polymerase chain reaction (PCR) technique, using species-specific primers. Test mixtures of meat were prepared by adding 5%, 2.5%, 1%, 0.5%, and 0.1% levels of pork, horse, cat, or dog meat to beef, sheep, and goat meat. Samples taken from those combinations were analyzed by PCR for species determination. Mitochondrial DNA (mt DNA) fragments of 439, 322, 274, 271, 225, 212, and 157 bp for horse, dog, cat, bovine, sheep, porcine, and goat meat, respectively, were amplified. PCR was conducted at 30 cycles for mixtures at the 5%, 2.5%, 1%, and 0.5% level, while at 35 cycles for mixtures at the 0.1% level. The results indicated that meat species were accurately determined in all combinations by PCR. It is concluded that PCR can be useful for fast, easy, and reliable control of adulterated consumer meat products.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Meat species mtDNA PCR